2002
DOI: 10.1002/1439-7633(20020301)3:2/3<250::aid-cbic250>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Design, Synthesis, and In Vitro Evaluation of Inhibitors for Prokaryotic tRNA-Guanine Transglycosylase: A Dramatic Sulfur Effect on Binding Affinity

Abstract: A lipophilic pocket at the tRNA‐guanine transglycosylase (TGT) enzyme active site was discovered and a substantial contribution to the substrate binding free energy was observed when this pocket was filled by apolar side chains. A family of new inhibitors of TGT was developed by employing the principles of molecular recognition and structure‐based de novo design, and shown to display up to submicromolar binding affinity. Two X‐ray structures of TGT–inhibitor complexes confirmed the binding mode predicted in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 23 publications
0
30
0
3
Order By: Relevance
“…Based on 1, systematic modifications resulted in potent micromolar TGT inhibitors, which also allowed the deciphering of some properties of the binding pocket ( Table 2, 11). 28,30,31 Here we report on the development of a new class of TGT inhibitors, based on scaffold 1 and extended by an imidazole moiety to reveal linbenzoguanine (6-aminoimidazol[4,5-g]quinazolin-8 (7H)-one) 4 (Table 1). This compound, prepared for the first time by Leonard et al 32 , was used as scaffold for substitutions in positions 3 and 4 with various aromatic side-chains to address a hydrophobic cleft formed by Val45, Leu68 and Val282 adjacent to the G 34 binding pocket (Table 2, 5-10).…”
Section: Introductionmentioning
confidence: 99%
“…Based on 1, systematic modifications resulted in potent micromolar TGT inhibitors, which also allowed the deciphering of some properties of the binding pocket ( Table 2, 11). 28,30,31 Here we report on the development of a new class of TGT inhibitors, based on scaffold 1 and extended by an imidazole moiety to reveal linbenzoguanine (6-aminoimidazol[4,5-g]quinazolin-8 (7H)-one) 4 (Table 1). This compound, prepared for the first time by Leonard et al 32 , was used as scaffold for substitutions in positions 3 and 4 with various aromatic side-chains to address a hydrophobic cleft formed by Val45, Leu68 and Val282 adjacent to the G 34 binding pocket (Table 2, 5-10).…”
Section: Introductionmentioning
confidence: 99%
“…In one such case this S…Aromatic (Tyr) interaction has been shown to stabilize the lipophilic region of the flexible substrate 2-carboxy-(R)-propyl-CoA in complex with methyl malonyl-CoA mutase (Mancia et al 1999). Also, the frequency of enzyme binding sites that involve sandwiching of an aromatic substrate between two hydrophobic fragments is striking (Meyer et al 2002;Wild et al 1997). The role of a highly conserved Met in substrate binding has been assessed by Folkers and coworkers in their studies on complexes of herpes simplex virus type 1 thymidine kinase with thymidine (Alber et al 1998;Pilger et al 1999), and a common sandwiching motif of the nucleobase between a Met and a Tyr residue in the active site of the enzyme for this system was revealed by X-ray crystallographic studies (Wild et al 1997).…”
Section: Secondary Structure and Non-covalent Interactionsmentioning
confidence: 99%
“…Further, the flexibility offered by the sidechain torsion angles; as revealed by the ability of the sidechain to fold onto itself facilitates the residue to adapt to partners of different shapes. Therefore, these residues (Met, Tyr) and the S-aromatic interaction may have a pivotal role to play in tubulin binding; possibly by the same mechanism as involved in enzyme binding by sandwiching of an aromatic substrate between two hydrophobic fragments (Meyer et al 2002). This is further supported by the fact that Met residues have been reported to be particularly useful in molecular recognition and binding sites of several proteins are rich in Met (Sebo et al 2000).…”
Section: Secondary Structure and Non-covalent Interactionsmentioning
confidence: 99%
“…A structure-based pharmacophore model was developed considering the H-bonding with a particular water molecule (W1) and virtual screening was successfully performed using a multistep workflow, including several hierarchical filters, pharmacophore-based screening using UNITY [127], and docking using FLEXX [128]. Pharmacophore-based virtual screening studies on this adapted protein conformation revealed novel chemical scaffolds active on TGT such as pteridine analogues [129] and quinazolinones [130]. For these structural classes water molecules (water displacement) represent a major aspect of ligand binding [131].…”
Section: Pharmacophore Modelingmentioning
confidence: 99%